PENOLAKAN TERHADAP KEGIATAN PENGADAAN TANAH MENURUT FIKIH DAN UNDANG-UNDANG INDONESIA - Artiyanto; Purwandari, Elce; Abbas, Syahrizal; Nurdin, Ridwan (TAHKIM, 2024)
ABSTRAK Rejection to Land Procurement activities for public interest purposes are complex issues that require an in-depth understanding from both Islamic law (fiqh) and Indonesian legislative perspectives. This study aims to identify the reasons for land rights holders' Rejection to Land Procurement and analyze the approaches used in fiqh and national law to address these Rejection. A qualitative method with a literature study approach was used in this research. Data collected includes primary, secondary, and tertiary legal materials relevant to Land Procurement issues and the rights of landholders. The study results indicate that, in Islamic fiqh, there is no standardized rule governing Rejection to Land Procurement; however, the principle of maslahat (benefit) serves as a primary basis for considering public interest without neglecting landholders' rights. On the other hand, Indonesian Law No. 2 of 2012 on Land Procurement for Development for Public Interest provides detailed procedures for handling Rejection, including provisions on compensation and legal recourse. In conclusion, fiqh offers greater flexibility based on government policy to balance individual rights with public interest, whereas Indonesian law is more structured in its regulatory resolutions. The novelty of this study lies in its comparative analysis between the normative fiqh approach and the positive law approach in Indonesia. This study recommends the integration of the maslahat principle within national legal practices to achieve fair resolutions and enhance awareness regarding land rights and obligations in the Land Procurement process. Keyword: Rejection, land procurement, fiqh, law legal